Transcranial Direct Current Stimulation Enhances Motor Skill Learning but Not Generalization in Chronic Stroke. (April 2018) - Hamoudi, Manuela; Schambra, Heidi M.; Fritsch, Brita; Schoechlin-Marx, Annika; Weiller, Cornelius; Cohen, Leonardo G.; Reis, Janine
Background . Motor training alone or combined with transcranial direct current stimulation (tDCS) positioned over the motor cortex (M1) improves motor function in chronic stroke. Currently, understanding of how tDCS influences the process of motor skill learning after stroke is lacking. Objective . To assess the effects of tDCS on the stages of motor skill learning and on generalization to untrained motor function. Methods . In this randomized, sham-controlled, blinded study of 56 mildly impaired chronic stroke patients, tDCS (anode over the ipsilesional M1 and cathode on the contralesional forehead) was applied during 5 days of training on an unfamiliar, challenging fine motor skill task (sequential visual isometric pinch force task). We assessed online and offline learning during the training period and retention over the following 4 months. We additionally assessed the generalization to untrained tasks. Results . With training alone (sham tDCS group), patients acquired a novel motor skill. This skill improved online, remained stable during the offline periods and was largely retained at follow-up. When tDCS was added to training (real tDCS group), motor skill significantly increased relative to sham, mostly in the online stage. Long-term retention was not affected by tDCS. Training effects generalized to untrained tasks, but those performance gains were not enhanced further by tDCS. Conclusions . Training of an unfamiliar skill task represents a strategy to improve fine motor function in chronic stroke. tDCS augments motor skill learning, but its additive effect is restricted to the trained skill.